Efficacy and safety of Gegen Qinlian decoction in the treatment of type II diabetes mellitus: a systematic review and meta-analysis of randomized clinical trials - Tan, YiMei; Liu, ShuangHua; Huang, MengHe; Cheng, Hui; Xu, BinBin; Luo, HongSheng; Tang, QiZhi (Frontiers in Endocrinology, 2024)
To systematically assess the efficacy and safety of Gegen Qinlian Decoction in the treatment of type 2 diabetes mellitus.We systematically searched a total of nine database from the time of creation to March 20, 2023. The quality of the literature was assessed using the risk of bias assessment tool in the Cochrane Handbook.RevMan 5. 3 and Stata 14.0 were applied to conduct Meta-analysis.Seventeen studies, encompassing 1476 patients, were included in the study. Gegen Qinlian Decoction combined with conventional treatment was found to significantly reduce FBG (MD = -0.69mmol/L, 95% CI -0.84 to -0.55, P < 0.01; I 2 =67%, P<0.01), 2hPG (MD = -0.97mmol/L, 95% CI -1.13 to -0.81, P < 0.01; I 2 =37%, P=0.09), HbA1c (MD = -0.65%, 95% CI -0.78 to -0.53, P < 0.01; I 2 =71%, P<0.01), TC (MD = -0.51mmol/L, 95% CI -0.62 to -0.41, P < 0.01; I 2 =45%, P=0.09), TG (MD = -0.17mmol/L, 95% CI -0.29 to -0.05, P < 0.01; I 2 =78%, P<0.01), LDL-C (MD = -0.38mmol/L, 95% CI -0.53 to -0.23, P < 0.01; I 2 =87%, P<0.01), HOMA-IR (SMD = -1.43, 95% CI -2.32 to -0.54, P < 0.01; I 2 =94%, P<0.01), and improve HDL-C (MD = 0.13mmol/L, 95% CI 0.09 to 0.17, P < 0.01; I 2 =30%, P=0.24).Only three studies explored the differences in efficacy between GQD alone and conventional treatment in improving glucose-lipid metabolism and insulin resistance, and some of the outcome indicators, such as 2hPG and HDL-C, were examined in only one study. Therefore, the effect of GQD alone on glucose-lipid metabolism and insulin resistance cannot be fully determined, and more high-quality studies are needed to verify it. Publication bias analysis revealed no bias in the included studies.Gegen Qinlian Decoction has certain efficacy and safety in enhancing glycolipid metabolism and alleviating insulin resistance, potentially serving as a complementary therapy for type 2 diabetes mellitus. Rigorous, large-sample, multicenter RCTs are needed to verify this.